Deteksi Resistensi Fluorokuinolon di Salmonella sp dengan Menggunakan Uji Kepekaan Asam Nalidiksat - Lim Bing Tiam; Tjan Sian Hwa; Sri Mulyani; Widiyani Widiyani; Diyah Asmawati; Prastika N; Meyra Fajarochwati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2011)
Fluoroquinolone is used as first line drug for Salmonella sp infection, but there were reports of increasing treatment failure with fluoroquinolone in infection caused by Salmonella sp, which in vitro is still succeptible to fluoroquinolone. The identification of nalidixic acid resistance, a first generation quinolone provides a high sensitivity and specifity for the detection of such fluoroquinolone resistance. The researchers aim is to study the prevalence and the minimum ciprofloxacin inhibitory concentration of nalidixic acid resistant but fluoroquinolone sensitive Salmonella sp at Premier Jatinegara Hospital. Blood cultures sent to Premier Jatinegara Hospital Laboratory during 2010 were evaluated according to Clinical and Laboratory Standards Institute guidelines. Identification and MIC succeptibility testing were determined by VITEK® 2 Compact (Biomerieux®) and nalidixic acid succeptibility testing was performed by disc diffusion method according to Kirby Bauer. Thirty eight Salmonella sp isolates were identified, all were succeptible to ciprofloxacin (MIC  0,25 mg/L), but 5 (13,2%) isolates were resistant to nalidixic acid and reported as resistant. This study found that 13,2% of Salmonella sp were resistant to fluoroquinolone but not detected by the recommended CLSI breakpoint values. The researchers recommend that nalidixic acid testing be included in Salmonella sp succeptibility testing in Indonesia and consider 3rd generation cephalosporin as the first line drug before a succeptibility test result is available.